Characterization and outcomes of gastroschisis in two institutions of a middle-income country in Cali, Colombia, between 2018 and 2022 - Torres-Muñoz, Javier; Figueroa-Gutierrrez, Luis Mauricio; Correa, Mariana Angel; Torres-Figueroa, Sofia; Ibarra Mera, Jose Feliz (Journal of Neonatal Surgery, 2024)
Background: Gastroschisis is the most common congenital defect of the abdominal wall. Its incidence has increased by 2 to 10 times worldwide. However, morbidity and mortality rates vary between high-, medium-, and low-income countries. Methods: This is an observational, cross-sectional study aimed at establishing the prevalence of gastroschisis in babies admitted to the intensive care units of the Clinica Versalles and the Hospital Universitario del Valle (HUV). Additionally, it is analytical, as it seeks to identify the clinical and surgical factors associated with the mortality of these neonates. Data were collected based on the information already recorded in the clinical histories of patients born or referred to these institutions between January 2018 and June 2022. Results: Fifty-six (56) babies were evaluated, with a birth rate corresponding to 1/1,000 live births. Of these, 35.70% were born to mothers under 19 years old, 55.36% came from municipalities other than Cali, and 91.07% were born at a gestational age greater than 32 weeks. Additionally, 58.90% were girls, with a median weight of 2,167 g (range: 1,440–3,240 g). Among the evaluated babies, 25% presented with complicated gastroschisis, and 44.64% had other malformations. The association between mortality outcomes and clinical factors showed that invasive mechanical ventilation for longer than 7 days increased the probability of death by 7.94 times, sepsis by 8.35 times, pulmonary hypertension by 7.14 times, acute kidney injury by 8.87 times, and pneumonia by 7.14 times. The surgical factors significantly associated with mortality were abdominal compartment syndrome (13.67 times), staged closure (9.17 times), more than two surgical interventions (7.80 times), failure to achieve closure (30.71 times), post-surgical complications (5.29 times), and intestinal ischemia (43 times). Conclusion: The rate of gastroschisis in this study is notably higher than that reported in other countries, with a substantial number of clinical and surgical complications significantly associated with mortality. Key factors influencing mortality include prolonged invasive mechanical ventilation, sepsis, pulmonary hypertension, acute kidney injury, and pneumonia. Surgical factors such as abdominal compartment syndrome, staged closure, multiple surgical interventions, failure to achieve closure, post-surgical complications, and intestinal ischemia also greatly increase the risk of death.